Religiao, politica e sociedade: contribuicao desde o pensamento do Papa Francisco para pensar o Brasil (2022)
Faced with the bicentennial of Brazil's independence, and with the problems and challenges that afflict our time, we question the role of religion and politics. The present article seeks to examine Pope Francis' thoughts on religion and politics, in order to help think about the Brazil we want for the present and the future. Initially, it addresses the importance of religion for building peace, overcoming violence and religious discrimination, for fraternity and caring for our common home. Next, politics is presented as a service to peace, justice, and solidarity, to the human person, to integral development, to the common home, and it explains the duty of lay Christians to participate in political life. The article concludes that dialogue and collaboration are necessary among the different reli- gious traditions, and between them and politics, for the promotion of a human, peaceful, just, sustainable and hopeful present and future.